The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1158/0008-5472.can-04-4562
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoic Acid Synthesis Gene ALDH1a2 Is a Candidate Tumor Suppressor in Prostate Cancer

Abstract: Prostate cancer is the most common cancer among men in the United States, and aberrant DNA methylation is known to be an early molecular event in its development. Here, we have used expression profiling to identify novel hypermethylated genes whose expression is induced by treatment of prostate cancer cell lines with the DNA methyltransferase inhibitor 5-Aza-2V-deoxycytidine (5-aza-dC). Of the 271 genes that were induced by 5-aza-dC treatment, 25 also displayed reduced expression in primary prostate tumors com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 47 publications
11
114
1
1
Order By: Relevance
“…In the present study, we investigated potential alterations in the RA pathway and analyzed their clinical relevance. In contrast to findings in other tumor entities, [7][8][9][10][11][12][13][14] we observed a marked up-regulation of key molecules associated with increased RA availability and alternative, prosurvival RA usage in gliomas. This was accompanied by increased intratumoral levels of RA precursors and activated RA.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated potential alterations in the RA pathway and analyzed their clinical relevance. In contrast to findings in other tumor entities, [7][8][9][10][11][12][13][14] we observed a marked up-regulation of key molecules associated with increased RA availability and alternative, prosurvival RA usage in gliomas. This was accompanied by increased intratumoral levels of RA precursors and activated RA.…”
contrasting
confidence: 99%
“…[7][8][9][10][11][12][13][14] In particular, epithelial tumors, which originate from tissues that depend on a closely orchestrated balance between cellular proliferation and subsequent differentiation, show loss of RA signaling components involved in RA availability. This frequently includes altered expression of cellular retinolbinding protein 1 (CRBP1), an intracellular transport protein in charge of facilitating the uptake of RA precursor molecules, [7][8][9] and of aldehyde dehydrogenase 1A1 (ALDH1A1), which is capable of activating RA precursors into the active RA metabolite, 10,11 as well as of cellular retinoic acid binding protein 2 (CRABP2) and cellular retinoic acid binding protein 1 (CRABP1), two chaperone proteins that shuttle between different cellular compartments channeling RA to designated nuclear RA receptors or to endosomal degradation by cytochrome P450, family 26 members (CYP26), respectively. [12][13][14] In addition, recent studies on breast tumor cells revealed a pathological involvement of the intracellular transport protein fatty acid binding protein 5 (FABP5) in neoplastic RA signaling.…”
mentioning
confidence: 99%
“…It functions as a detoxifying enzyme and has been proposed as a common marker for both normal and malignant stem and progenitor cells (17,19,27). ALDH1 activity has been employed successfully as a stem cell marker in retinoblastoma, prostate, pancreas and breast cancer (20,(28)(29)(30). The current study demonstrated that both human osteosarcoma MG63 and human fibrosarcoma HT1080 contained subpopulations with high ALDH activity, approximately 10% of the total cell population, as determined by Aldefluor assay.…”
Section: Discussionmentioning
confidence: 62%
“…ALDH1A2 encodes an enzyme responsible for the synthesis of retinoic acid, a compound with prodifferentiation properties. ALDH1A2 is identified to be a candidate TSG in prostate cancer whose expression is induced by DNA demethylation, which is reduced in prostate tumors compared with normal prostate, and negatively correlated with tumor-free survival (57). A further study indicate that ALDH1A2 is involved in apoptosis in bladder cancer cells (58), and has significant effects on cell proliferation and drug resistance in leukemia (59,60) and lung cancer cell lines (59).…”
Section: Discussionmentioning
confidence: 96%